Serological analysis of herpes simplex virus types 1 and 2 with monoclonal antibodies. - Pereira, L (1982)
A panel of monoclonal antibodies to herpes simplex virus glycoproteins was used for serological analysis of 130 strains. Based on specific immunological determinants, strains of each serotype clustered into subgroups. Monoclonal antibodies were suitable reagents for serotyping and have potential application to epidemiology of herpes simplex virus infections.